Volume 4B: Combustion, Fuels and Emissions 2014
DOI: 10.1115/gt2014-26162
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Jets in Subsonic Air Crossflow at Elevated Pressure

Abstract: The breakup, penetration, droplet size and size distribution of a Jet A-1 fuel in air crossflow has been investigated with focus given to the impact of surrounding air pressure. Data has been collected by Particle Doppler Phased Analyzer (PDPA), Mie-Scattering with high speed photography augmented by laser sheet, and Mie-Scattering with ICCD Camera augmented by nano-pulse lamp. Nozzle orifice diameter, do, was 0.508 mm and nozzle orifice length to diameter ratio, lo/do, was 5.5. Air crossflow velocities ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Experimentally, it has been observed that more viscous liquid jets are deflected laterally by the cross flow, more than the less viscous jets. 14,15,40 An interpretation of this observation can be based on the more developed liquid velocity radial profile in the more viscous liquid jet.…”
Section: Temporal Developmentmentioning
confidence: 99%
“…Experimentally, it has been observed that more viscous liquid jets are deflected laterally by the cross flow, more than the less viscous jets. 14,15,40 An interpretation of this observation can be based on the more developed liquid velocity radial profile in the more viscous liquid jet.…”
Section: Temporal Developmentmentioning
confidence: 99%